Natural Language Understanding of Malayalam Language - Usha, K; Pandian, S Lakshmana (International Journal of Computer Sciences and Engineering, 2025)
Natural Language Understanding (NLU) is really challenging sub domain of language processing as far as any highly agglutinative and morphologically rich south Indian Languages are concerned. It requires highly complex procedures and techniques to extract its inflections and grammatical information, thereby make a computer to understand the real sense of the language as human beings does. This paper aims not only providing insights into natural language understanding but also gathers information about the various existing techniques in Malayalam Language. Natural language Understanding refers to the understanding of any language by a machine with the help of an intermediate representation. Here we have briefed the various techniques and algorithms used with Morphological Analyzer, POS tagger, chunking, Parsing, Named Entity Recognition, and Word Sense Disambiguation which are the inevitable components for understanding any Natural Language.